Allelic variants of the Melanocortin 4 receptor (MC4R) gene in a South African study group. Issue 1 (23rd October 2015) - Logan, Murray; Van der Merwe, Maria‐Teresa; Dodgen, Tyren M.; Myburgh, Renier; Eloff, Arinda; Alessandrini, Marco; Pepper, Michael S.
Abstract: Obesity is a global epidemic that results in significant morbidity and mortality. Mutations in the melanocortin 4 receptor ( MC4R ) gene, which codes for a G‐protein‐coupled receptor responsible for postprandial satiety signaling, have been associated with monogenic obesity. The prevalence of obesity is on the increase in South Africa, and it is hypothesized that mutations in MC4R are a contributing factor. The aim of this study was to perform a retrospective assessment of the relationship between allelic variants of MC4R and BMI in a South African study cohort. DNA was isolated from a demographically representative cohort of 297 individuals and the entire MC4R gene sequenced by Sanger sequencing. Eight previously reported MC4R variants were identified in 42 of the 297 (14.1%) study participants. The most frequently observed MC4R alleles were V103I (4.0%), I170V (1.5%), and I198I (1.2%), while the remaining five variants together constituted 1.18%. Five compound heterozygotes were also detected. Although MC4R variants were rare, the majority of variation was observed in individuals of Black African ancestry. No statistically significant associations with BMI were reported. Given that lifestyle interventions have limited success in decreasing obesity, there is an urgent need to perform large‐scale population studies to further elucidate the molecular underpinnings of this disease. Abstract : Analysis of MC4R in a demographically representative cohort of the South African population revealed the presence of eight previously identified single nucleotide variants.